Isocryptolepine, an indoloquinoline alkaloid from Cryptolepis sanguinolenta promotes LDL uptake in HepG2 cells - Aggrey,Mike Okweesi (2018)
ABSTRACT About 31 percent of deaths worldwide result from atherosclerotic cardiovascular disease. Hyperlipidemia remains the major risk factor for this disease and therefore, it is necessary to identify antihyperlipidemic compounds for drug development. The crude ethanolic extract of Cryptolepis sanguinolenta (Lindl.) Schltr., Apocynaceae, has demonstrated antihyperlipidemic properties. However, the chemical constituents responsible for this action are unknown. Hence, to identify chemical constituent(s) of C. sanguinolenta with anti-hyperlipidemic effect, five indoloquinoline alkaloids were isolated and evaluated in 1,1′-dioctadecyl-3,3,3′,3′-tetramethyl-indocarbocyanine perchlorate labeled low density lipoprotein uptake assay using HepG2 cells. The minor alkaloid, isocryptolepine, showed strong activity in promoting low lipid lipoprotein uptake by 1.85-fold. Isocryptolepine may, therefore, serve as a lead compound for future studies in the development of novel antihyperlipidemic drugs.